Spectral Properties of Circular Piezoelectric Unimorphs - PUSTKA, Martin; PŮST, Ladislav (Archives of Acoustics, 2017)
The piezoelectric unimorphs are essential resonant components of many oscillating systems including electroacoustic devices. The unimorph spectral properties are namely dependent on geometric dimensions, applied materials and mounting. Preliminary dimensioning and optimization of unimorph shape are usually carried out prior to comprehensive design work mostly based on finite element method. Simple analytical model is a suitable tool for initial design phase. This paper presents a derivation of calculation model describing natural vibrations of a circular unimorph with the piezoelectric layer diameter smaller than the elastic layer diameter. The system of equations with closed-form solution is instrumental to calculation of resonant frequencies and mode shapes for unimorphs with clamped, simply supported and free circumference. The theoretical results are compared with vibration velocity measurement of clamped unimorph sample in a wide frequency range. Analytical model derived in this paper is used to assess the effect of the thickness tolerance on unimorph resonant frequencies.